Fabrication of Co0.85Se@CN double-walled hollow cages to address the volume expansion of anode and enhance ion diffusion for sodium-ion storage. (10th September 2022) - Yu, Dengfeng; Yang, Bo; Liang, Huimin; Zhao, Gongyuan; Zhang, Hong; Wang, Yuanlin; Sun, Ye; Yu, Miao
Abstract: Constructing hollow-structured materials is an efficient route to address the volume expansion of anode and enhance ion diffusion for sodium-ion battery (SIB). Superior to the single-walled products, multi-walled hollow-structured anode materials possess more storage sites, enhanced robustness, and higher volumetric capacity; nevertheless, synthesis of the multi-walled hollow structure often requires harsh synthesis conditionand complicated etching process. Herein, we report fabrication of Co0.85 Se double-walled hollow cages coated by a nitrogen-doped carbon layer (Co0.85 Se@CN) as high-performance anode materials for SIB. Using ZIF-67 as precursor, a facile ion exchange strategy is employed with no aid of high temperature treatment and complex etching process. The resultant Co0.85 Se@CN exhibit distinct double-walled hollow structure with abundant lacunas on the walls, which increases the accessible area, shortens the ion transport path and most importantly provides appropriate buffer space against volume expansion. Moreover, the C protective layer on both sides of the inner- and outer-walls further benefits high conductivity, chemical stability, and robustness during charge/discharge process. As a result, the Co0.85 Se@CN anode deliver a high reversible capacity of 402 mAh g –1 at 50 mA g –1 and 316 mAh g –1 at 100 mA g –1 after 100 cycles for SIB. Graphical abstract: Image, graphical abstract